Abrahamic Reflections on Randomness and Providence - Clark, Kelly James; Koperski, Jeffrey; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This open access book addresses the question of how God can providentially govern apparently ungovernable randomness. Medieval theologians confidently held that God is provident, that is, God is the ultimate cause of or is responsible for everything that happens. However, scientific advances since the 19th century pose serious challenges to traditional views of providence. From Darwinian evolution to quantum mechanics, randomness has become an essential part of the scientific worldview. An interdisciplinary team of Muslim, Christian and Jewish scholars$1 (Bbiologists, physicists, philosophers and theologians$1 (Baddresses questions of randomness and providence. Kelly James Clark is author, co-author, or editor of more than 30 books including Religion and the Sciences of Origins, Strangers, Neighbors Friends: Muslim-Christian-Jewish Reflections on Compassion and Peace, and Abraham$1 (Bs Children: Liberty and Tolerance in an Age of Religious Conflict. Jeffrey Koperski is Professor of Philosophy at Saginaw Valley State University. He is the author of The Physics of Theism: God, Physics, and the Philosophy of Science, and Divine Action, Determinism, and the Laws of Nature.s
Part I Introduction -- 1. Randomness and Providence: Is God a Bowler or a Curler? -- Part II The Problem(s) Stated -- 2. The Many Faces of Randomness -- 3. Randomness and Providence: Defining the Problem(s) -- Part III Science -- 4. Randomness in the Cosmos -- 5. Randomness, Providence, and the Multiverse -- 6. Can a Muslim be an Evolutionist? -- 7. Chance, Evolution, and the Metaphysical Implications of Paleontological Practice -- Part IV The Abrahamic Faiths -- 8. Judaism and Providence -- 9. Randomness and Providence in Christian Thought -- 10. God, Cosmos, and Humanity: Muslim Perspectives on Divine Providence -- Part V Providence and Chance -- 11. Reconciling Meticulous Divine Providence with Objective Chance -- 12. Creatio Continua and Quantum Randomness -- 13. Causality, Indeterminacy, and Providence: Contemporary Islamic Perspectives from Said Nursi and Basil Altaie -- 14. Divine Action and the Emergence ofFour Kinds of Randomness -- 15. God et al.$1 (BWorld-Making as Collaborative Improvisation: New Metaphors for Open Theists -- 16. Saadia on (3z(Bwhat is in the hearts of people when they reach the limits of endurance in a trial(3y (B-- 17. Randomness, Causation, and Divine Responsibility.s
Keywords: Religions; Religion -- Philosophy; Theology; Comparative Religion; Philosophy of Religion; Christian Theology